2021
DOI: 10.3390/su13136987
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the Regional Sustainable Developmental Role of Universities—From the Multilevel-Perspective (MLP) and Beyond

Abstract: This article establishes the multilevel perspective (MLP) as one of the main research approaches in transition research to study complex systemic change processes in socio-technical systems at different structural levels. The application of the MLP to the higher education system, especially to conceptualize the transition of universities towards a sustainable (regional) developmental role, is still in its infancy. Through using a descriptive narrative analysis of seminal articles, the results of the four-years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 72 publications
0
12
0
2
Order By: Relevance
“…Therein, extant studies discuss several dimensions and activities that HEIs use to contribute to sustainability (Peer and Stoeglehner 2013;Purcell et al 2019;Radinger-Peer and Pflitsch 2017;Trencher et al 2014;Zilahy et al 2009). However, the manifold forms of participation seem rather fragmented and institutionally supported knowledge transfer and knowledge intermediaries usually play a minor role (Blume et al 2017;Radinger-Peer et al 2021). Our study allows us to make several contributions to this discussion.…”
Section: Heis In Regional Transition Processesmentioning
confidence: 87%
See 1 more Smart Citation
“…Therein, extant studies discuss several dimensions and activities that HEIs use to contribute to sustainability (Peer and Stoeglehner 2013;Purcell et al 2019;Radinger-Peer and Pflitsch 2017;Trencher et al 2014;Zilahy et al 2009). However, the manifold forms of participation seem rather fragmented and institutionally supported knowledge transfer and knowledge intermediaries usually play a minor role (Blume et al 2017;Radinger-Peer et al 2021). Our study allows us to make several contributions to this discussion.…”
Section: Heis In Regional Transition Processesmentioning
confidence: 87%
“…These activities comprise different forms of informal engagement in non-academic contexts that call for a certain level of institutionalization and can support the ongoing knowledge exchange between academic and non-academic actors required for both transition processes (Radinger-Peer and Pflitsch 2017) and the emergence of transdisciplinary projects as a driver of transition processes (Stephens et al 2008). However, hitherto, the roles of HEIs in regional development processes have been assessed mostly from an economic perspective (Radinger-Peer et al 2021). As HEIs and their intermediaries often focus their activities on the promotion of technological innovation processes, they lack the specialized resources and capabilities to promote the commercialization of sustainability-related inventions (Kivimaa et al 2017).…”
Section: Heis and Knowledge Intermediaries In Regional Transitionsmentioning
confidence: 99%
“…As purveyors of knowledge in society, universities have, quite understandably come under pressure to assume leading roles in the transition toward sustainable futures (Cortese, 2003;Leal Filho, 2011;Awuzie and Emuze, 2017;Ramakrishna et al, 2020). Accordingly, universities are expected to cater toward deepening sustainability-oriented education, innovations, and sustainable regional development (Peer and Stoeglehner, 2013;Soares et al, 2020;Thomas and Pugh, 2020;Garcia-Alvarez-Coque et al, 2021;Radinger-Peer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…From this, another question arises: "Where do we find transversal organizational vehicles that may bring together bottom up and top-down approaches to foster SDG-oriented transformations?" Higher Education Institutions (HEIs) have a promising convening potential that may make them especially adequate for this purpose (Birch et al, 2013;Ehlenz, 2018;Radinger-Peer et al, 2021). HEIs are actors that are well-placed to create and maintain collaborative intermediary vehicles that rely upon i) the combination of expert knowledge, youth talent and intangible assets such as legitimacy or neutrality, and ii) their independence and capacity to develop their own strategic SDG-oriented programs (Moreno-Serna et al, 2020a; 2021).…”
Section: Agradecimientosmentioning
confidence: 99%
“…HEIs are increasingly being called upon to play an active role in SDG partnerships thanks to their potential to concert bottom-up and top-down approaches (Birch et al, 2013;Ehlenz, 2018;Radinger-Peer et al, 2021). A second research gap thus emerges which centers upon ongoing discussions regarding the specificities of the role of HEIs in intermediary and multi-stakeholder arrangements (Findler et The purpose of this research is to address both the research gaps identified above using a methodology that combines intervention and interpretation.…”
Section: 14- Purpose Of This Thesismentioning
confidence: 99%